2003
DOI: 10.1038/sj.onc.1206778
|View full text |Cite
|
Sign up to set email alerts
|

Proteolytic regulation of Forkhead transcription factor FOXO3a by caspase-3-like proteases

Abstract: Forkhead family transcription factors are critical regulators of cell cycle progression and apoptosis in hematopoietic cells. Here, we show that FOXO3a (also known as FKHRL1) is a new substrate of caspase-3-like proteases during apoptosis in T lymphocytes. FOXO3a was cleaved in vivo by caspases in leukemic Jurkat cells following engagement of Fas (CD95) receptor, staurosporine, and etoposide treatment, but not following engagement of CD99, a caspase-independent cell death inducer. Caspasemediated cleavage of F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
67
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(68 citation statements)
references
References 41 publications
1
67
0
Order By: Relevance
“…We speculate that cytoplasmic FOXO3a may serve as a crucial anti-oxidant reservoir in prostate cancer and this FOXO3a stocking may be a NAD þ dependent process and regulated by NAMPT. FOXO3a protein can be degraded by AKTtriggered ubiquitination-proteasome pathway (Plas and Thompson, 2003) or by caspase-3-like proteases in hematopoietic cells (Charvet et al, 2003). Recently, it is shown that N-terminal acetylation of cellular proteins creates specific degradation signals targeted by ubiquitin-dependent proteasome pathway (Hwang et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…We speculate that cytoplasmic FOXO3a may serve as a crucial anti-oxidant reservoir in prostate cancer and this FOXO3a stocking may be a NAD þ dependent process and regulated by NAMPT. FOXO3a protein can be degraded by AKTtriggered ubiquitination-proteasome pathway (Plas and Thompson, 2003) or by caspase-3-like proteases in hematopoietic cells (Charvet et al, 2003). Recently, it is shown that N-terminal acetylation of cellular proteins creates specific degradation signals targeted by ubiquitin-dependent proteasome pathway (Hwang et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Regulation of caspase 3 -like activity by EPO also has recently been linked to a unique regulatory mechanism that blocks the proteolytic degradation of phosphorylated forkhead transcription factors by caspase 3. Given that specific proapoptotic transcription factors, such as FoxO3a, have been shown to be a substrate for caspase 3-like proteases at the consensus sequence DELD 304 A (Charvet, et al, 2003), studies have shown that blockade of caspase 3 -like activity prevents the destruction of the inactive phosphorylated FoxO3a during oxidative stress to increase cell survival ).…”
Section: Epo and Cellular Signal Transductionmentioning
confidence: 99%
“…Regulation of caspase 3 -like activity by EPO also has recently been linked to a unique regulatory mechanism that blocks the proteolytic degradation of phosphorylated forkhead transcription factors by caspase 3. Given that specific proapoptotic transcription factors, such as FoxO3a, have been shown to be a substrate for caspase 3-like proteases at the consensus sequence DELD 304 A (Charvet, et al, 2003), studies have shown that blockade of caspase 3 -like activity prevents the destruction of the inactive phosphorylated FoxO3a during oxidative stress to increase cell survival (Chong and Maiese, 2007a).Akt also is associated with proteins are derived from the Drosophila Wingless (Wg) and the mouse Int-1 genes , Li, et al, 2006c, Speese and Budnik, 2007 (Li, et al, 2005, Li, et al, 2006c, Maiese, et al., 2008d.Wnt proteins are generally divided into functional classes based on their ability to induce a secondary body axis in Xenopus embryos and to activate certain signaling cascades that consist of the Wnt1 class and the Wnt5a class (Maiese, 2008b, Maiese, et al, 2008d. These involve intracellular signaling pathways are critical for Wnt signal transduction (Maiese, 2008a, Maiese, 2008b.…”
mentioning
confidence: 99%
“…First, caspase-generated fragments of PARP-1 can interact with Nuclear Factor kappa B (NFkappaB) subunits and enhance NFkappaB transcriptional activity (Lamkanfi et al, 2006), a transcription factor present in the nucleus of postnatal reactive astrocytes (Acarin et al, 2000b). Second, cleavage of FoxO transcription factors, like FoxO3a, that contain a conserved caspase-3 cleavage site (Charvet et al, 2003), could also play a role in the modulation of gene expression during glial differentiation or astrogliosis. Third, it has been suggested that caspase-3 could serve as a mechanism of protein degradation required for the cellular response to changes in extrinsic signals (McLaughlin, 2004).…”
Section: Cleaved Caspase-3 Is Found In the Astroglial Nucleimentioning
confidence: 99%